مظاهر التدخل الدولي للحد من التلوث البيئي - لطفاوي، محمد عبدالباسط (جامعة زيان عاشور الجلفة, 2020)
One of the most important requirements of the modern era is the issue of protecting the environment from pollution, and the mechanisms to reduce or reduce the risks incurred by it resulting from various types of pollution. Also a major dimension of the challenges facing countries, especially in planning for sustainable environmental development. With a view to positively dealing with environmental problems that are trying hard to find possible solutions. It prompted the international system to take measures and mechanisms to prepare and respond to pollution accidents in various regions of the world, whether it comes to water, air or soil as a result of the negative effects of the industrial renaissance and technological progress and lack of Countries ’compliance with legislation related to environmental protection.
أضحت قضية حماية البيئة من التلوث والآليات الكفيلة بالحد أو التقليل من المخاطر المحدقة بها والناتجة عن مختلف أنواع التلوث، أحد أهم متطلبات العصر الحديث. وبعدًا رئيسا من أبعاد التحديات التي تواجهها الدول، خاصة في التخطيط للتنمية البيئية المستدامة. حيث استخدمنا المنهج الوصفي التحليلي للتصدي لموضوع بحثنا هذا من خلال إظهار وتبيان التعامل الدولي مع المشاكل البيئية والتي تحاول جاهدة أن تجد لها الحلول الممكنة، ومما نستنتجه أن ظاهرة التلوث دفعت بالمنظومة الدولية لاتخاذ التدابير والآليات الكفيلة بالاستعداد والتصدي لحوادث التلوث في مختلف مناطق العالم، سواء تعلق الأمر بالماء أو الهواء أو التربة نتيجة للآثار السلبية الناجمة عن النهضة الصناعية والتقدم التكنولوجي وعدم التزام الدول بالتشريعات المتعلقة بحماية البيئة.
Keywords: حماية البيئة -- القانون الدولي -- القوانين والتشريعات